Media Technologies and Their Role in the Information Warfare - Fedorov, V A; Borhsenius, A V (Vestnik Rossijskogo universiteta družby narodov. Seriâ Politologiâ (Online), 2016)
The article analyzes the new role of the mass media in the modern information space, the basic techniques and technologies of focused preparation, semantic distortion and emotional coloring of the transmitted information. The value of the mass media is estimated as the main weapon of the information warfare in the modern geopolitical space. Specific examples and techniques for manipulating information.